Organic Electrosynthesis: Applications in Complex Molecule Synthesis - Shatskiy, Andrey; Lundberg, Helena; Kärkäs, Markus D. (ChemElectroChem, 2019)
Organic electrosynthesis is an enabling and sustainable technology, which constitutes a rapidly expanding field of research. Electrochemical approaches serve as convenient and green alternatives to stoichiometric and toxic chemical redox agents. Electrosynthesis constitutes a promising platform for harnessing the unique reactivity profiles of radical intermediates, expediting the development of new reaction manifolds. This Review highlights both anodic and cathodic methods for the construction of various kinds of complex molecules. So radical! Free radical intermediates have received increasing appreciation because of their unique reactivity profile. Organic electrosynthesis constitutes a promising platform for harnessing the unique reactivity profiles of radical intermediates. This review outlines key applications of electrochemical redox reactions in complex molecule synthesis.